Decline in Cardiovascular Mortality: Possible Causes and Implications. Issue 2 (20th January 2017) - Mensah, George A.; Wei, Gina S.; Sorlie, Paul D.; Fine, Lawrence J.; Rosenberg, Yves; Kaufmann, Peter G.; Mussolino, Michael E.; Hsu, Lucy L.; Addou, Ebyan; Engelgau, Michael M.; Gordon, David
Abstract : If the control of infectious diseases was the public health success story of the first half of the 20th century, then the decline in mortality from coronary heart disease and stroke has been the success story of the century's past 4 decades. The early phase of this decline in coronary heart disease and stroke was unexpected and controversial when first reported in the mid-1970s, having followed 60 years of gradual increase as the US population aged. However, in 1978, the participants in a conference convened by the National Heart, Lung, and Blood Institute concluded that a significant recent downtick in coronary heart disease and stroke mortality rates had definitely occurred, at least in the US Since 1978, a sharp decline in mortality rates from coronary heart disease and stroke has become unmistakable throughout the industrialized world, with age-adjusted mortality rates having declined to about one third of their 1960s baseline by 2000. Models have shown that this remarkable decline has been fueled by rapid progress in both prevention and treatment, including precipitous declines in cigarette smoking, improvements in hypertension treatment and control, widespread use of statins to lower circulating cholesterol levels, and the development and timely use of thrombolysis and stents in acute coronary syndrome to limit or prevent infarction. However, despite the huge growth in knowledge and advances in prevention and treatment, there remain many questions about this decline. In fact, there is evidence that the rate of decline may have abated and may even be showing early signs of reversal in some population groups. The National Heart, Lung, and Blood Institute, through a request for information, is soliciting input that could inform a follow-up conference on or near the 40th anniversary of the original landmark conference to further explore these trends in cardiovascular mortality in the context of what has come before and what may lie ahead.